The Effect of Acupuncture Therapy on Blood Oxygen Saturation in Patients with Blood Pressure Disorders and Coughs in Elderly Health Post, Surakarta - Sumanto Sumanto; Listina Ade Widya Ningtyas (Masters Program in Public Health, 2022)
Background: One way to detect functional disorders of respiration, heart, blood vessels, and muscle oxidative mechanisms is to check blood gas saturation using a pulse oximeter, especially during the COVID-19 pandemic. Acupuncture is one of the management of health problems at the promotive level, preventing functional disorders of the respiratory system, cardiovascular system, and oxidative muscle rehabilitative which is used to improve health status, especially those who experience changes in blood gas saturation due to chronic cough, hypertension, hypotension, and muscle fatigue. The aim of the study was to determine the effect of acupuncture therapy on peripheral blood oxygen saturation (peripheral SpO2) in patients with a history of respiratory system disorders and blood pressure disorders, especially old age at the Surakarta Health Post.Subjects dan Method: The form of the research was pre-experimental (quasi-experimental), using two groups of pre-test and post-test purposive samples totaling 20 people. Dependent variable Oxygen saturation. The independent variable was acupuncture therapy. Data were analyzed using Wilcoxon's test.Results: Peripheral blood oxygen saturation values were higher in the intervention group before the intervention (Mean= 83.00; SD= 11.59) than after the intervention (Mean= 82.00; SD= 7.53) and not statistically significant (p= 0.294).Conclusion: Acupuncture therapy reduces blood gas saturation values in patients with blood pressure and cough disorders. Keywords: acupuncture therapy, peripheral blood gas saturation, pulse oximeter, history of cough, blood pressure disorders. Correspondence:Listina Ade Widya Ningtyas. Poltekkes Kemenkes Surakarta. Jl. Letjend Sutoyo Mojosongo, Surakarta, Central Java. Email: ade.widya23@gmail.com. Mobile: 085647300048